Intersections between interprofessional practice, cultural competency and primary healthcare. Issue 5 (17th May 2013) - Oelke, Nelly D.; Thurston, Wilfreda E.; Arthur, Nancy
Abstract: The concepts of interprofessional collaborative practice (IPCP), cultural competency and primary healthcare (PHC) appear to be linked in theory and practice. This discussion article provides arguments explicating the potential linkages between IPCP and cultural competency. We argue that cultural competency is an important component of IPCP both for relationships with patients and/or communities in which providers work and between team members. Organizational structures also play an important role in facilitating IPCP and cultural competency. The integration of both IPCP and cultural competency has the potential to enhance positive health outcomes. Furthermore, we argue IPCP and cultural competency have important implications for PHC service design, given interprofessional teams are a key component of PHC systems. Linking these concepts in providing PHC services can be essential for impacting outcomes at all levels of primary healthcare, including patient, provider and systems.